Design, solid-phase synthesis and evaluation of enterobactin analogs for iron delivery into the human pathogen Campylobacter jejuni. Issue 19 (15th October 2018) - Zamora, Cristina Y.; Madec, Amaël G.E.; Neumann, Wilma; Nolan, Elizabeth M.; Imperiali, Barbara
Graphical abstract: Abstract: The human enteropathogen Campylobacter jejuni, like many bacteria, employs siderophores such as enterobactin for cellular uptake of ferric iron. This transport process has been shown to be essential for virulence and presents an attractive opportunity for further study of the permissiveness of this pathway to small-molecule intervention and as inspiration for the development of synthetic carriers that may effectively transport cargo into Gram-negative bacteria. In this work, we have developed a facile and robust microscale assay to measure growth recovery of C. jejuni NCTC 11168 in liquid culture as a result of ferric iron uptake. In parallel, we have established the solid-phase synthesis of catecholamide compounds modeled on enterobactin fragments. Applying these methodological developments, we show that small synthetic iron chelators of minimal dimensions provide ferric iron to C. jejuni with equal or greater efficiency than enterobactin.